2016
DOI: 10.1249/mss.0000000000000992
|View full text |Cite
|
Sign up to set email alerts
|

Increased Visual Use in Chronic Ankle Instability

Abstract: On the basis of our systematic review with meta-analysis, it appears that CAI patients do not use somatosensory information to the same extent as uninjured controls and instead upregulate the use of visual information during single limb stance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 51 publications
7
69
0
Order By: Relevance
“…Changes in PostCG cortical activation during single-limb stance showed that somatosensory perceptions may be affected among those with CAI compared with copers. Similarly, in a recent meta-analysis, Song et al 24 found that use of somatosensory perceptions was altered among individuals with CAI. Specifically, individuals with CAI tended to rely on vision more than and may integrate sensory information differently from those without a history of ankle sprain.…”
Section: Discussionmentioning
confidence: 83%
“…Changes in PostCG cortical activation during single-limb stance showed that somatosensory perceptions may be affected among those with CAI compared with copers. Similarly, in a recent meta-analysis, Song et al 24 found that use of somatosensory perceptions was altered among individuals with CAI. Specifically, individuals with CAI tended to rely on vision more than and may integrate sensory information differently from those without a history of ankle sprain.…”
Section: Discussionmentioning
confidence: 83%
“…72 The ability to integrate different sensory inputs appears to be compromised in CAI. Song et al 73 performed a metaanalysis to investigate postural control in eyes-open and eyes-closed positions. Compared with healthy controls, patients with CAI relied more heavily on visual information than somatosensory information during unipedal-stance balance tasks.…”
Section: Sensory-perceptual Impairmentsmentioning
confidence: 99%
“…After suffering an LAS, the ligaments, muscles, and receptors surrounding the ankle joint become damaged, causing decreased function within that ankle [11]. Postural control is controlled by a number of body functions including neuromuscular, proprioceptive, and sensorimotor control [2,19]. The CAI population demon-strated higher force plate measurements than the healthy population during the single-leg balance (SLB) test [17].…”
Section: Introductionmentioning
confidence: 99%
“…SLBs with EO have shown that CAI individuals have increased foot lift, different COP strategies, and increased time to balance measurements when compared to healthy individuals [13]. An SLB with EC is much harder to complete compared with EO because an individual relies heavily on their proprioceptive and sensorimotor functions when trying to balance themselves in a normal balancing task [19]. CAI individuals have exhibited increased postural sway, increased BES, and increased time to balance measurements in EC tests compared to healthy individuals [19].…”
Section: Introductionmentioning
confidence: 99%